2009
DOI: 10.1161/hypertensionaha.109.134023
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Chronic Baroreceptor Stimulation on the Autonomic Cardiovascular Regulation in Patients With Drug-Resistant Arterial Hypertension

Abstract: Abstract-In patients with drug-resistant hypertension, chronic electric stimulation of the carotid baroreflex is an investigational therapy for blood pressure reduction. We hypothesized that changes in cardiac autonomic regulation can be demonstrated in response to chronic baroreceptor stimulation, and we analyzed the correlation with blood pressure changes. Twenty-one patients with drug-resistant hypertension were prospectively included in a substudy of the Device Based Therapy in Hypertension Trial. Heart ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
91
1
12

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 153 publications
(109 citation statements)
references
References 36 publications
5
91
1
12
Order By: Relevance
“…10 Recent clinical interventions showing impressive blood pressure lowering effects by targeting reductions in SNA [11][12][13][14] and progress in the elucidation of the central sympathetic regulatory pathways altered in hypertension [15][16][17] are part of a renaissance of interest in the control of the sympathetic nervous system…”
Section: The Sympathetic Renaissancementioning
confidence: 99%
See 3 more Smart Citations
“…10 Recent clinical interventions showing impressive blood pressure lowering effects by targeting reductions in SNA [11][12][13][14] and progress in the elucidation of the central sympathetic regulatory pathways altered in hypertension [15][16][17] are part of a renaissance of interest in the control of the sympathetic nervous system…”
Section: The Sympathetic Renaissancementioning
confidence: 99%
“…98 Following animal studies first conducted over 50 years ago 99,100 and extensive technical development work, 101,102 surgical implantation of a device eliciting chronic carotid baroreflex stimulation (Rheo, CVRx, Minneapolis, MN, USA) has recently been demonstrated to effectively lower blood pressure and muscle SNA in humans. 14,71,72,103,104 This has been based on the recently resurrected idea that arterial baroreceptors control arterial pressure in the long term. 105 In his original study, Thrasher (2002) showed that unloading of baroreceptors at one carotid sinus (with all other arterial baroreceptors denervated) caused a sustained pressor response lasting up to 3 weeks in conscious dogs.…”
Section: Drug-resistant Hypertension-how To Treat?mentioning
confidence: 99%
See 2 more Smart Citations
“…In a canine animal model, Lohmeier et al could demonstrate that activation of the baroreflex at the carotid artery by implanted pacemaker was able to reduce blood pressure as well as serum catecholamine levels [67,68]. This approach is currently in clinical evaluation for resistant hypertension [69]. Promising data from a clinical trial for baroreflex activation therapy has been published recently.…”
Section: Baroreflex Activation Therapymentioning
confidence: 99%